JUMLAH TRAKEA PADA DAUN Ludwigia adscendens (L.) Hara DALAM KONDISI TERGENANG : SEBUAH GEJALA PLASTISITAS ANATOMI - Joko Budiono (The East Java Biological Society, 1999)
This study was conducted to reveal the influence of waterlogging on the number of tracheas in each vascular bundle of Ludwigia adscendens (L.) Hara leaf. This plant is well known as aquatic weed which can grow floating on water surface. The leaf primordium extend across the water from 10-15 cm below water surface. The plant was grown in aquarium at 0, 10 and 15 cm water depth. The observed leaves were first, third and fifth the base. Anatomical structure were analyzed using serial cross sections of he leaf the cross section were made by paraffin method. The data were analyzed using ANOVA and DMRT method. The result showed that significance difference on the number of tracheas in each vascular bundle were found among leaves of different depth.